Efektywność elementarnej edukacji matematycznej wspomaganej komputerowo w pracy korekcyjno-wyrównawczej - Kaczmarek, Żanetta (Wydawnictwo Naukowe UAM w Poznaniu, 2003)
The main subject of this work is the elementary mathematical education, however, not in the context of lesson’s process but as a realisation in corrective-levelling forms for children who at the beginning of their school career have specific difficulties in understanding mathematical terms. This phenomenon is getting more and more common - we can even speak about a specific mathematical phobia. In this article I want to demonstrate the results of investigation trying to find an answer to the questions: 1) what kind of influence has the teaching which is assisted with a computer for the elimination of difficulties for children aged 7-10 in mathematical education taking place in corrective levelling lessons, 2) in what scale education assisting with a computer during corrective-levelling lessons fulfils motivation function for children in younger school age according to overcome difficulties in mathematical education. So, the subject of this investigation is to examine the efficiency of the didactic-educational process taking place in corrective levelling lessons and examine the probable influence of the computer on the sphere of attitude in the process of elimination of educational difficulties.
The effectiveness of computer-assisted elementary mathematics education in corrective-compensation work